2002
DOI: 10.1210/jc.2002-020032
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis and Proliferation of Human Testicular Somatic and Germ Cells during Prepuberty: High Rate of Testicular Growth in Newborns Mediated by Decreased Apoptosis

Abstract: Programmed cell death and proliferation are evolutionary conserved processes that play a major role during normal development and homeostasis. In the testis, during the fetal and newborn periods, they might determine final adult size and fertility potential. In the present study, we have measured the relative number of testicular cells in apoptosis and in active proliferation in the seminiferous cords and in the interstitium, at different age periods of prepubertal testicular development in humans. Testes from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(39 citation statements)
references
References 24 publications
5
32
0
2
Order By: Relevance
“…However, these observations are uncertain due to the small number and variable technical quality of these hardto-get human samples. Nevertheless, such a pattern of FGFR3 expression mimics roughly the proliferation profile of germ cells throughout development (Berensztein et al, 2002;Honecker et al, …”
Section: Discussionmentioning
confidence: 97%
“…However, these observations are uncertain due to the small number and variable technical quality of these hardto-get human samples. Nevertheless, such a pattern of FGFR3 expression mimics roughly the proliferation profile of germ cells throughout development (Berensztein et al, 2002;Honecker et al, …”
Section: Discussionmentioning
confidence: 97%
“…Another difference resides in the fact that rodent gonocyte undergoes two phases of proliferation in the fetal and neonatal periods, respectively, separated by a proportionally long period of quiescence, whereas humans and marmosets lack this quiescent phase, and instead, one can find proliferative gonocytes in all periods surveyed, from gestation weeks (GWs) 12-14 until 2.5-4 months after birth in human, albeit at various levels (Hilscher & Engemann 1992, Berensztein et al 2002, Honecker et al 2004, Ewen et al 2013. Overall, these studies reported the highest rates of proliferation between the third and fifth gestation months, followed by decreased proliferation in late gestation and a small increase in proliferation in 2.5-to 6-month-old infants.…”
Section: Insights From Non-rodent Speciesmentioning
confidence: 99%
“…After the 6th month after delivery, the spermatogonia decrease in number in parallel to decreased gonadotropins. Activity in the GnRH pulse generator which lasts from the neonatal period to the middle infancy (mini puberty) is important for criptorchidism and the spermatogenic function and fertility in advanced years (20,(23)(24)(25)(26)(27). In addition, it is thought that increased level of testosterone provides masculinization of the brain an determines cognitive functions, sexual behavior and sexual orientation in relation (4,28).…”
Section: Mini Puberty and Its Interpretation Invited Reviewmentioning
confidence: 99%